ANALISA KINERJA SISTEM KONTROL DISKRIT CHAOS LUP TERBUKA DAN TERTUTUP DENGAN PENGENDALI IMPULSIF - Utomo, Robertus Heri Soelistyo; Widowati, Widowati; Munawwaroh, Dita Anies; Asnawi, Yuliyan Hambyah (MATEMATIKA, 2017)
tability the discrete chaotic systems is interesting to be discussed, given that chaos is closely related to random and irregular state. Stability of discrete chaotic system can be obtained using impulsive control law and applying Lyapunov stability theory. So it can show sufficient conditions for the design of impulsive controllers andÂ globally exponentially set-stable can be reached. Based on the results of the impulsiveÂ control, it is seen that the behavior of chaos in a discrete chaos system which originally the trajectory are irregular, can be control and become stable, and there is a globally exponentially attracting set earned in the system. The numerical simulation on the discrete chaotic system is presented to illustrate the effectiveness of the obtained results from control impulsive.